Oral corticosteroid use, morbidity and mortality in asthma: A nationwide prospective cohort study in Sweden. Issue 11 (11th June 2019) - Ekström, Magnus; Nwaru, Bright I.; Hasvold, Pål; Wiklund, Fredrik; Telg, Gunilla; Janson, Christer
Abstract: Background: Patterns and determinants of long‐term oral corticosteroid (OCS) use in asthma and related morbidity and mortality are not well‐described. In a nationwide asthma cohort in Sweden, we evaluated the patterns and determinants of OCS use and risks of OCS‐related morbidities and mortality. Methods: Data for 217 993 asthma patients (aged ≥ 6 years) in secondary care were identified between 2007 and 2014 using Swedish national health registries. OCS use at baseline was categorized: regular users (≥5 mg/d/y; n = 3299; 1.5%); periodic users (>0 but <5 mg/d/y; n = 49 930; 22.9%); and nonusers (0 mg/d/y; n = 164 765; 75.6%). Relative risks of becoming a regular OCS user and for morbidity and mortality were analysed using multivariable Cox regression. Results: At baseline, 24% of asthma patients had used OCS during the last year and 1.5% were regular users. Of those not using OCS at baseline, 26% collected at least one OCS prescription and 1.3% became regular OCS users for at least 1 year during the median follow‐up of 5.3 years. Age at asthma diagnosis, increasing GINA severity and Charlson Comorbidity Index were associated with regular OCS use. Compared to periodic and non‐OCS use, regular use was associated with increased incidence of OCS‐related morbidities and greater all‐cause mortality, adjusted HR 1.34 (95% CI 1.24‐1.45). Conclusions: Oral corticosteroids use is frequent for asthma patients, and many are regular users. Regular OCS use is associated with increased risk of morbidity and mortality. These findings indicate that there is a need of other treatment options for patients with severe asthma who are using regular OCS. Abstract : Annually, almost one in seven asthma patients used oral corticosteroids, which was stable over the 10‐year study period. Oral corticosteroids are still a substantial part of current asthma management for many patients and are associated with severe side effects and mortality risk. There is a need for other treatments for severe asthma patients who are using regular oral corticosteroids.